General Anestesi pada Pasien Laparatomi Tumor Hepar - Muhammad Ezyra Widya Aqshal; Anna Millizia (Lembaga Pengembangan Kinerja Dosen, 2026)
Chronic liver disease is a significant health problem and places a significant burden on healthcare services. Deaths from complications of chronic liver disease (cirrhosis and cancer) account for approximately 3.5% of all deaths worldwide each year. Hepatocellular carcinoma (HCC) is a primary liver tumor, accounting for 90% of all liver tumors. Due to limitations in liver transplantation, liver resection is considered the treatment of choice for HCC patients with a single tumor and sufficient liver function reserve. Liver resection and transplantation are the only curative treatment options available for HCC patients. Surgical procedures require anesthesia. General anesthesia is the preferred method for liver tumor resection. There are five main classes of anesthetic agents: intravenous (IV) anesthetics, inhalational anesthetics, IV sedatives, synthetic opioids, and neuromuscular blocking agents. Estimated health risks depend on the extent or severity of liver disease, the nature and timing of surgery, the type of anesthesia, and other comorbidities.